Pemanfaatan aplikasi nelayan pintar di Kabupaten Pati – Jawa Tengah - Indah Susilowati; Mudjahirin Thohir; Nugroho SBM; Ika Suciati (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2020)
Fishermen live with uncertainty because of their livelihood relating to the nature directly so that fishermen have to be able to adapt and mitigate with the significantly climate change nowadays. There are many ICT innovations developed to help fishermen’s fishing activities. One of them made and developed by Marine and Fisheries Ministry is Nelayan Pintar (Nelpin) application. The aims of this study are to analyze fishermen’s perception toward Nelpin apps, to analyze fishermen’s willingness using Nelpin apps, and to analyze strategy to increase Nelpin apps utilization. The analysis unit of this study is fishermen domiciling in Juwana districts. This study uses mixed method approach used to analyze the data by conducting deep interview to the respondents. Stakeholder analysis is used to explain strategy helped by Atlas.TI Apps. Descriptive-statistics and chi-square trial are used to explain respondents’ social-economy and the willingness to accept. This analysis result is that fishermen need Nelpin apps to help fishing activities. They consider that Nelpin apps is useful and easy to use. Most of them said that they will use Nelpin application. The strategy to increase Nelpin utilization is by conducting pilot project related to the apps implementation and giving supporting facilities and infrastructures.